2019
DOI: 10.1111/pai.13141
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of microarray B‐cell epitope mapping in food allergies: A systematic review

Abstract: Background: Peptide microarray technology has been proposed as a useful tool for diagnosing food allergy. However, there is considerable heterogeneity in the clinical methods and analytical procedures used to assess its diagnostic and prognostic performance. We performed a systematic review of studies that have used B-cell epitopes by peptide microarray in food allergies to identify the clinical utility of this immunologic technique.Methods: Studies were screened in PubMed, Web of Science, and Embase according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…51,52 The evidence of clinical utility of such tests has been recently systematically reviewed. 53,54 The most recent studies have focused on peanut [55][56][57][58] and cow's milk 59,60 allergies as well as allergies to shellfish [61][62][63] and legumes. [64][65][66] Using a peptide microarray, Caubet et al 60 identified a greater intensity and broader diversity of IgE binding in children with persistent CMA, which decreased as children became tolerant.…”
Section: Specific Ige To Allergen Epitopesmentioning
confidence: 99%
“…51,52 The evidence of clinical utility of such tests has been recently systematically reviewed. 53,54 The most recent studies have focused on peanut [55][56][57][58] and cow's milk 59,60 allergies as well as allergies to shellfish [61][62][63] and legumes. [64][65][66] Using a peptide microarray, Caubet et al 60 identified a greater intensity and broader diversity of IgE binding in children with persistent CMA, which decreased as children became tolerant.…”
Section: Specific Ige To Allergen Epitopesmentioning
confidence: 99%
“…Milk allergy represents a major burden for food-allergic children, 11,12 and further insight into the cross-reactivity of specific major allergens will allow better understanding of mechanisms of allergy, or tolerance induction involving major epitopes. 13 Chronic granulomatous disease (CGD) is a rare but severe primary immunodeficiency caused by defects in the genes coding for essential proteins involved in leucocyte phagocytosis. Hematopoietic stem cell transplantation is the only definitive treatment that can cure CGD.…”
Section: Kana Ram Jatmentioning
confidence: 99%
“…Also, the competitive ELISA suggested the presence of common epitopes further investigated by amino acid sequencing. Milk allergy represents a major burden for food‐allergic children, 11,12 and further insight into the cross‐reactivity of specific major allergens will allow better understanding of mechanisms of allergy, or tolerance induction involving major epitopes 13
…”
mentioning
confidence: 99%
“…Each SNR value was then converted into modified z-scores which are calculated using median and median absolute deviation (MAD) rather than mean and standard deviation. Z-scores represent a standardized signal intensity and are frequently used to report immunoglobulin binding to peptide microarray [53]. Median and MAD were calculated for each patient and leader sequence combination.…”
Section: Statistical Analysis Of Microarray Datamentioning
confidence: 99%